The effect of smart coatings on the radiation passing through glazing / Masoud Kamalisarvestani - Masoud, Kamalisarvestani (2012)
Windows provide us with natural light and fine-looking connections to the outdoors. However, a huge amount of energy is lost through these building envelopes. This study reviews the most common and contemporary coatings of the glass surface with thin films. Through this review the various types of intelligent coatings are compared in terms of their performance in saving air-conditioning and electrical lighting energy. Having completed the review, it is determined that electrochromic and thermochromic windows consume less than around 40 kWh/m2 for electric lighting energy and around 10 kWh/m2 for cooling energy.Therefore,these two types feature better performance compared to other smart windows.The thermochromic effect of vanadium dioxide (VO2) thin films has inspired many research teams to apply this type of smart thin films as a promising coating for windows leading to drastic reductions in lighting and ventilation energy. In this study vanadium dioxide thin films have been deposited on clear glass by RF magnetron sputtering. Different film thicknesses (20 nm, 50 nm, 80 nm and 120 nm) were deposited by altering the sputtering duration. The films were characterized for their crystal structure and surface morphology by means of X-Ray Diffractometer (XRD) and Field Emission Scanning Electron Microscope (FESEM). The reflectance and transmittance of samples were measured before and after transition temperature using a UV-Vis-NIR spectrophotometer. Finally, the thermochromic behavior of the samples is compared.The 50 nm sample exhibited better reflective behavior at room temperature, greater reflectance difference (-5.6 %) in the visible range and highest thermochromic efficiency (ɳ (2200 nm) = 54.3%). By the same token, the 80 nm sample performed the best in increasing the reflectance (6.7 %) in near-IR range. However, the thickness should be selected according to the glazing requirements and the priority of visible or near-IR optical properties.